The problem of pro-Russianism of the Polish national minority in Lithuania after 2014 - Bobier, Artur (Mundus Slavicus I, 2025)
In the independent state of Lithuanians, a small Baltic nation, the two largest national minorities were Slavic groups – Poles and Russians. Attempts to protect the Lithuanian language and to rewrite the history of Lithuania caused disputes over the right to use one’s own surname and the use of language by minorities. The similar position of the two largest minorities was a common denominator, abstracting from the relations between the two nations in the international arena. Numerous pro-Russian statements by representatives of the Electoral Action of Poles in Lithuania are a controversial topic, especially in a country so afraid of Russian aggression.